2019
DOI: 10.1155/2019/2598727
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Influence of Water-Shale Interaction on Stress Sensitivity of Organic-Rich Shale

Abstract: Shale reservoirs are characterized by low permeability and natural fractures. In the process of reservoir development, the working fluid enters the reservoir. This may result in the formation of new fractures or expansion of natural fractures. When shale reservoirs are exploited, the fluid pressure in the fracture or pore is reduced. This destroys the stress balance of the reservoir, produces stress sensitivity damage, and reduces the reservoir permeability. Organic-rich shale from the Yanchang Formation, Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Using empirical, numerical simulations, petrographic observations, and the ability to restructure the diagenetic process, the authors concluded that reservoir formation petrophysical properties can be predicted. Additionally, Liu et al (2019) examined the effect shale and water interface on the sensitivity of stress on shale rock rich in organic materials. Shale reservoirs were found to have natural fractures and low permeability based on the study results.…”
Section: Pore Volume Porosity and Permeabilitymentioning
confidence: 99%
“…Using empirical, numerical simulations, petrographic observations, and the ability to restructure the diagenetic process, the authors concluded that reservoir formation petrophysical properties can be predicted. Additionally, Liu et al (2019) examined the effect shale and water interface on the sensitivity of stress on shale rock rich in organic materials. Shale reservoirs were found to have natural fractures and low permeability based on the study results.…”
Section: Pore Volume Porosity and Permeabilitymentioning
confidence: 99%
“…Authigenic quartz is positively correlated with brittleness, while detrital quartz have little or no effect. Liu et al 32 suggested that, during exploitation, the fluid pressure in fracture/pore gets reduced. This pressure drop disturbs the stress balance of the reservoir, leading to a permeability reduction.…”
Section: Some Important Parameters That Definementioning
confidence: 99%
“…Shale gas formation has strong water sensitivity [1,2] and developes fractures [1,3]. The problem of wellbore collapse is still very serious when using the commonly used strong inhibition and strong plugging oil-based drilling fluid in the drilling process of long horizontal sections [4], and the risk of sticking is great [5].…”
Section: Introductionmentioning
confidence: 99%